The Place of a Child on Platforms: Responsibilities, Obligations, and Expectations - Divon, T.; Annabell, T.; Goanta, C.; Abidin, Crystal; Beuckels, E.; Hudders, L.; Van den Abeele, E.; de Brabandere, M.; Vanwesenbeeck, I.; De Jans, S.; Leaver, Tama; Livingstone, S.; et al. (2025)
This panel delves into the complex entanglement of children within our 'platform society,' spotlighting their roles amidst the dynamics of platformisation, datafication, and monetisation. It scrutinises the emergence of child influencers, mapping their integration and active participation within the influencer economy. This exploration underscores the critical intersection between childhood and platformization, highlighting the commodification and monetization practices shaping children's presence on platforms. The panel seeks to understand these practices across diverse contexts, including time, platforms, geographies, and cultures, emphasizing the multifaceted roles of children as consumers, producers, and actors. The panel also examines regulatory frameworks surrounding children on platforms, focusing on governance issues related to child labour, advertising, and platform liability. It navigates the tension between viewing children as 'becomings' in need of protection and as 'beings' with an agency, contributing to the discourse on platform governance and regulatory practices. Presenting a range of papers, the panel traverses topics from the monetization of children in influencer content on TikTok, to the offering of a child influencer taxonomy, to the influence of kidfluencers on young viewers' consumption behaviors. It critically assesses the impact of digital dashboards on parenting, illustrating how children's health, location, and well-being are intertwined with datafication logic. Collectively, these papers illuminate how the place of children online is contested, as they become embroiled in practices of monetisation, visibility, and datafication across platforms and infrastructures. Our panellists draw from their empirical and theoretical work to challenge these practices, emphasising their implications for platform governance and addressing how regulations can serve children's best interests.